Efektivitas Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Dalam Meningkatkan Produktivitas Penelitian Ilmiah Dosen di Institut PTIQ Jakarta - Sugiharto, Sugiharto; Shunhaji, Akhmad; Sarnoto, Ahmad Zain (El-Idare, 2023)
This research aims to analyze the Effectiveness of the LPPM Institut PTIQ Jakarta in Improving the Productivity of Scientific Research for Lecturers. This research was conducted using a descriptive qualitative research method, employing instruments such as questionnaires, interviews, observations, and documentation. The results and conclusions of this research indicate several things. First, the LPPM of PTIQ Jakarta has met the five criteria set by Gibson, namely clear objectives, well-planned programs, appropriate program development, available facilities and infrastructure, and a system of supervision and control. Second, there was a significant decrease in the number of research projects in 2022 compared to 2021. This was due to a policy change from individual research to collaborative research. Collaborative research aims to provide encouragement and motivation for lecturers who have not been involved in research activities to collaborate on research projects within their respective faculties. This step is expected to bring significant benefits. Inexperienced lecturers will have a golden opportunity to learn from experts and practitioners in their field, enhance their methodological skills, and develop the analytical abilities needed to conduct high-quality research.